Impact of the MitraClip Procedure on Left Atrial Strain and Strain Rate. (March 2018) - Gucuk Ipek, Esra; Singh, Siddharth; Viloria, Esperanza; Feldman, Ted; Grayburn, Paul; Foster, Elyse; Qasim, Atif
Abstract : Background—: Although reverse remodeling of the left atrium (LA) has been shown after MitraClip placement in degenerative mitral regurgitation (MR), changes in LA strain and strain rate have not been evaluated in these patients or compared with surgical mitral valve repair. Methods and Results—: We included 87 subjects (mean age 59.7±12.3 years) with degenerative MR enrolled in the randomized EVEREST II trial (Endovascular Valve Edge-to-Edge Repair Study II). Baseline peak positive LA strain (ε) and strain rates along with longitudinal left ventricular strain (LV ε) were compared with 12-month follow-up measures. At 12 months, all 38 mitral valve repair subjects had ⩽2+ MR, and 31 of the 49 MitraClip had ⩽2+ MR. Baseline LA strain and strain rate values were similar in MitraClip and mitral valve repair groups. Of the strain rate measures, only peak early diastolic strain rate was consistently decreased in all treatment arms. In patients with reduced baseline LA ε, no significant change in LA ε occurred in either the MitraClip or mitral valve repair group despite significant MR and LA volume reduction. However, in patients with normal or high baseline ε, successful MR reduction by either method resulted in return of LA ε to normative values. There was a significant correlation between LA ε, LV ε values, and change in LA ε and LV ε over time. Conclusions—: Changes seen in LA ε seem to depend on baseline LA and LV function. Changes in LA ε after MR reduction may reflect a decrease in LA expansion but may also be influenced by the degree of pre-existing LA dysfunction. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT00209274. Abstract : Supplemental Digital Content is available in the text.